Quo Vadis in Anatomical Research? Preserving the Conditions for Discovery in an Era of Predictable Outcomes - Joe Iwanaga; Shane Tubbs (Clinical Anatomy, 2026)
ABSTRACT Contemporary anatomical research has become increasingly integrated with clinical practice, generating substantial benefits for patient care and strengthening the translational relevance of the discipline. At the same time, some of the most influential anatomical advances have emerged from investigations whose eventual significance could not have been predicted when they were undertaken. This viewpoint argues that anatomical research generates overlapping descriptive, explanatory, operational, and conceptual contributions whose value may emerge across different timescales. Although contemporary funding, publication, and academic evaluation systems understandably favor research with predictable and measurable outcomes, such priorities may inadvertently discourage concept‐generating inquiry whose broader significance becomes apparent only retrospectively. Anatomical discovery depends not only on observation and increasingly sophisticated technologies, but also on interpretation, recognition of anomalies, and willingness to reconsider established frameworks. Artificial intelligence and computational approaches may accelerate data acquisition, quantitative analysis, and pattern detection, but these capabilities do not by themselves constitute anatomical understanding. Preserving the future capacity for discovery therefore requires both intellectual and institutional conditions that support rigorous inquiry even when its eventual significance cannot be predicted. The future of anatomy should not be framed as a choice between operational and conceptual contributions, but as a need to preserve the diversity of inquiry through which anatomical knowledge continues to evolve.